Posttranscriptional changes of serum albumin: Clinical and prognostic significance in hospitalized patients with cirrhosis. Issue 6 (3rd November 2014) - Domenicali, Marco; Baldassarre, Maurizio; Giannone, Ferdinando A; Naldi, Marina; Mastroroberto, Marianna; Biselli, Maurizio; Laggetta, Maristella; Patrono, Daniela; Bertucci, Carlo; Bernardi, Mauro; Caraceni, Paolo
<x xml:space="preserve">Abstract</x> Beside the regulation of fluid distribution, human serum albumin (HSA) carries other activities, such as binding, transport, and detoxification of many molecules. In patients with cirrhosis, HSA exhibits posttranscriptional alterations that likely affect its functions. This study aimed at identifying the structural HSA alterations occurring in cirrhosis and determining their relationship with specific clinical complications and patient survival. One hundred sixty‐eight patients with cirrhosis, 35 with stable conditions and 133 hospitalized for acute clinical complications, and 94 healthy controls were enrolled. Posttranscriptional HSA molecular changes were identified and quantified by using a high‐performance liquid chromatography/electrospray ionization mass spectrometry technique. Clinical and biochemical parameters were also recorded and hospitalized patients were followed for up to 1 year. Seven HSA isoforms carrying one or more posttranscriptional changes were identified. Altered HSA isoforms were significantly more represented in patients than in healthy controls. Conversely, the native, unchanged HSA isoform was significantly reduced in cirrhosis. Native HSA and most altered isoforms correlated with both Child‐Pugh and Model for End‐Stage Liver Disease scores. In hospitalized patients, oxidized and N‐terminal truncated isoforms were independently associated with ascites, renal impairment, and bacterial infection. Finally, the native HSA and cysteinylated/N‐terminal truncated isoforms were predictors of 1‐year survival, with greater prognostic accuracy than total serum albumin concentration. Conclusions: Extensive posttranscriptional changes of HSA, involving several molecular sites and increasing in parallel with disease severity, occur in patients with cirrhosis. Altered isoforms are independently associated with specific clinical complications, whereas the residual, native HSA isoform independently predicts patient survival. These findings support the concept of the "effective albumin concentration, " which implies that the global HSA function is related not only to its serum concentration, but also to the preservation of its structural integrity. (Hepatology 2014;60:1850–1859)